Serum cystatin C and serum creatinine levels in type 2 diabetes mellitus - AS, Ashwin Kumar; AS, Anil kumar (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes mellitus is a metabolic disorder resulting from deficient insulin secretion, inefficient insulin action or both leading to chronic hyperglycemia. Diabetic complications result from the toxic effects of chronic hyperglycemia combined with other metabolic derangements. Diabetic nephropathy eventually leads to loss of kidney function, which is the most common cause of End stage renal disease. Measurement of GFR is an important parameter in assessing kidney function for which Creatinine is currently being used despite its inherent fallacies. Cystatin C is an alternative marker with some advantages. Aims and objectives: To measure the serum cystatin C levels in type 2 diabetes mellitus patients. To compare serum cystatin C levels with serum creatinine levels in type 2 diabetes mellitus patients. Methods: The study was carried out in 30 type-2 diabetic patients and 30 non-diabetic controls, in the age group of 35 to 75 years. Both the groups were age and gender matched. Serum cystatin C levels and serum creatinine levels were measured in both the groups. Serum creatinine was estimated by Jaffe’s kinetic method, while the estimation of serum cystatin C was done by Immunoturbidimetric method. Results: Serum creatinine as well as serum cystatin C levels were significantly elevated in the study group as compared to non-diabetic controls. There was a strong positive correlation of serum cystatin C with serum creatinine. Conclusion: Serum cystatin C can be used as an alternative to serum creatinine in determining GFR in type 2 diabetes mellitus.